PRO-KONTRA KREMASI DALAM PERSPEKTIF IMAN KATOLIK DI GEREJA HATI KUDUS YESUS TANAH MAS SEMARANG - Bambang Bianto; Martinus (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2020)
The development of the era that demands fast-paced actions today has an effect on all human activities. This influence also causes the method of cremation of corpses at the Tanah Mas Church of the Sacred Heart to be increasingly known and used in today's funerals, as an alternative to the old method of burying the bodies in the ground. The purpose of this study is to describe the problems that occur between agreeing to cremation and those who still maintain the old way by burying the bodies into the ground, these problems are understood in the light of the Catholic faith at the Sacred Heart of Jesus Parish Tanah Mas Semarang. The study was conducted on 32 people consisting of members of the Church Council, Prodiacon, Head of the Environment, Elderly, Head of Liturgy, Diakonia, Koikonia and Catechists at the Tanah Mas Church of the Sacred Heart, Semarang. The variables of this study include those who are cremated, buried in the ground, carried out because of traditions or customs that apply among the families, or people have other reasons. Data obtained by questionnaires and interviews. The data obtained were processed with the Validator's assessment criteria sorted into a rating scale. Interview data were processed with descriptive statistics, which can describe the situation of the people's choice in general. The results showed that cremation has become a common practice in funerals at the Hati Kudus Tanah Mas Catholic Church, Semarang with 59% of respondents saying they agree and as many as 84% of respondents admit that nowadays cremation is more practical and economical as a method of burial of corpses. Meanwhile, the results of other questionnaires regarding cremation show that knowledge of the faith of the people regarding the resurrection of the body at the end of time is 84% ​​of respondents saying it has no effect.